The Effectiveness Of Scramble In Improving Reading Comprehension At SMP Negeri 5 Ranoyapo - Junita Waworuntu, Junita Waworuntu; Hampp, Paula; Kumayas, Tirza A. (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of this study is to examine the effectiveness of scramble in improving students' reading comprehension at SMP Negeri 5 Ranoyapo. Using a quantitative pre-experimental design, the study involved 23 students who participated in the pre-test and post-test. Multiple-choice tests are used to measure students' reading comprehension before and after treatment. The pre-test results showed an average score of 56.73, while the post-test results increased significantly to 83.43. This substantial increase in scores suggests that scramble techniques positively affect students' reading comprehension.. The findings suggest that implementing the scramble technique in reading instruction can enhance students' ability to understand texts more effectively. Therefore, it can be concluded that this technique is a beneficial teaching strategy for improving reading comprehension in students.